LANGUAGE AND CULTURE: AN ANALYSIS FROM THE PERSPECTIVE OF LINGUOCULTUROLOGY TEACHING - Mamatsoliyeva Sevinchoy Khamza kizi (TADQIQOTLAR, 2025)
Annotation: This article analyzes the relationship between language and culture from the perspective of linguoculturology. The science of linguoculturology studies the inextricable link between language and culture and aims to study the linguistic expression of national mentality, traditions and values. The article examines issues such as vocabulary, phraseological units, metaphors, translation problems, and changes in language and culture under the influence of globalization. This study highlights the place of linguoculturology in the field of linguistics and education, and provides important theoretical and practical recommendations for language learners and translators.